Philosophical Education as Subjectivation Practice in the Prison Context: Considerations through the Medium of Foucault (Nóema, 2023)
This article explores the concept of philosophical education as a practice of subjectivation within the total institutions system. Drawing inspiration from the work of Michel Foucault, the author delves into the transformative potential of philosophical knowledge in shaping individual behaviour and fostering self-affection. The analysis highlights the relationship between philosophical knowledge and power discourse, emphasizing the concept of subjectivation as a means to modify the balance of forces between external domination and individual self-governance. Offering tools for reflection and ethical transformation, philosophical education can serve as an exercise of resistance and liberation from oppressive and degrading systems. The article concludes by discussing the possible implications of this perspective with reference to the prison system and within penal institutions.
Keywords: subjectivation; total institutions; critical education; prison system; ethical transformation